The Effect of Multi-Years Reclaimed Water Irrigation on Dryland Carbon Sequestration in the North China Plain - Yanbing Chi (MDPI AG, 2021)
Reclaimed water is an alternative water source which could alleviate the shortage of water resources in agricultural systems. Many researchers have studied the effect of reclaimed water on soil environment, crop yield, etc. However, carbon sequestration in reclaimed water irrigated agricultural systems is less studied. This study investigates methane uptake and photosynthesis in reclaimed water irrigation systems contributing to carbon sequestration estimation and analyzes the important factors impacting them. The results show that CH4 uptake is related to soil water-filled pore space (WFPS) with a quadratic and it has the highest uptake when WFPS is between 40 and 50%. Long-term reclaimed water irrigation could significantly decrease (p < 0.05) CH4 uptake and macroaggregate stability in the topsoil. However, reclaimed water had no significant impact on photosynthesis in comparison. The type of fertilizer is an important factor which impacts CH4 emission from soil; urea had a lower CH4 uptake and a higher CO2 emission than slow-released fertilizer. Overall, reclaimed water irrigation could effectively decrease soil carbon sequestration. A soil wetted proportion level of 40–50% was recommended in this study for favorable methane oxidation. Slow-released fertilizer in reclaimed water irrigated agriculture could better control soil carbon emission and soil carbon absorption.